Aplikasi Medan Magnet pada Sistem Hidroponik NFT terhadap Pertumbuhan dan Hasil Sawi - Setiyono Setiyono; Danu Dwiharjo; Ayu Puspita Arum (Agrosains : Jurnal Penelitian Agronomi, 2022)
The demand for mustard consumption continues to increase, which encourages an increase in mustard production which is not proportional to the area of agricultural land so that cultivation with an NFT Hydroponic system is needed with the application of a magnetic field as a solution to this problem. Which the magnetic field can accelerate growth and water absorbtion. The purp ose of this study was to determine the interaction of magnetic field application with varieties on the growth and yield of mustard using the NFT hydroponic system. This experiment used a split-plot design consisting of 2 factors and 3 replications. The magnetic field application as the main plot consisted of 2 levels, without magnetic field application (M0) and magnetic field application (M1), while the varieties as sub-plots consisted of 5 levels, Tosakan (V1), Shinta (V2), Dakota (V3), IRR(V4) and Nauli F1 (V5). The observation variables were plant height, number of leaves, fresh weight, dry weight, and root volume. The results showed, there was a significant interaction only on the number of leaves with the best treatment M1V5 (16 number of leaves). The magnetic field factor significantly affected all growth and production variables of mustard except dry weight.